ARSITEKTUR DVD (Digital Virtual Design) - Danny Santoso Mintorogo (DIMENSI (Journal of Architecture and Built Environment), 2000)
Soon after the millennium year of 2000 and toward 21th century, the ways of architecture design will be a great change from traditional hand design and drawings to super computer digital virtual design models with tremendous of high-end architectural 3D software domains. Virtual Technology will be a plus to architectural design stage to obtain several "scheme" and observe with real - time feedback of the quality (height, light, furniture), shape, and environment as well as the sequential of the space, site context or massing studies. Abstract in Bahasa Indonesia : Strategi dalam desain arsitektur pada abad 22 atau setelah tahun milinium 2000 ini akan banyak didominasi dengan perangkap teknologi canggih yang tentunya akan mengandalkan pada perangkap keras (komputer) dan perangkap lunak (software) untuk tujuan desain arsitektur secara digital. Teknologi "Virtual" akan dimanfaatkan untuk bidang arsitektur dalam mengoptimasikan disain arsitektur secara digital maya, untuk mengobservasi/mengkaji kwalitas ruang, model suatu ruang/massa secara maya dalam phase perancangan arsitektur. Kata kunci: arsitektur, desain, digital, maya.